Potential Amplifiable Areas in Dhaka City for Seismic Hazard - Rashied, Masudur; Mahmud, Md Akter (Journal of Bangladesh Institute of Planners, 2019)
After 1990s the population of Dhaka accelerated rapidly due to its economic and political influence with many other pull factors. Historically, the city grew along with the shore of River Buriganga and its surrounding areas. Later on, the city expanded towards its north, east and south-eastern parts. A significant number of canals, khals, and water bodies are infilled with sand, especially in the peripheral areas of the city. Dhaka is one of the most seismically vulnerable cities in the world for its location since it is close to Eurasian and Indian plates. From the lithological aspect, the core city has developed on Upper and Lower Madhupur Terrace with surrounding Holocene floodplains. The soil profile of the floodplain shows the near-surface soil up to a depth of 30m mostly composed of alluvial sandy and clayey soils with a probable chance of soil amplification. The empirical correlation between Standard Penetration Test (SPT) and shear wave velocity (Vs) is a popular approach for estimating the amplification factor. This paper gathered secondary information from existing literature to illustrate the potential amplifiable areas in Dhaka city and compare it with the gradual shrinkage of water bodies for seismic hazard. JBIP, Vol. 12, 2019 (Printed in June 2020), pp. 33-43